BASIC WILDERNESS SURVIVAL SKILLS - Angier, Bradford (Lyons Press, 2018)
From building fires to building shelters, the best advice from expert survivalist Bradford Angier all in one handy guide, newly revised and updated. For everyone, whether familiar with the outdoors or not, there may come a time when you will need to know how to stay alive in the backcountry. Author Bradford Angier and editor Maryann Karinch set these basic, crucial skills out for you in clear and concise language. The book comprises a broad selection of skills, and both novice and expert alike can master them. Newly revised and updated!